The supply response of rainfed agricultural crops to price changes in South Darfur State, Sudan - Mohamed, El Agib F.; El Mahi, Sauod H. (المجلة الزراعية; مجلد 5 عدد 2 (2007), 2007)
The objective of this study is to examine the supply response of rainfed agricultural crops to price changes in South Darfur State. The study was based on data collected for the period 1987- 2004. The data included area, production, rainfall, and relative prices. The analysis of data was based on the Nerlovian partial adjustment model. The results revealed that the supply response of individual crops was positive but generally low in the short-run and fairly high in the long-run. These results could be a useful tool for policies intended to enhance the production efficiency of rainfed agriculture in the State. The study also demonstrated the importance of having adequate and timely adoption of agricultural technology to promote the low response of individual crops and to maintain a sustainable food security for the State.